FOUNDATIONS OF ADULT EDUCATION - Keja-Kaereho, Charlene (IJRDO- Journal of Educational Research, 2016)
In recent years, much has been said about lifelong learning around the world.In both developed and developing nations, changes in work organization andmanagement, coupled with a focus on markets, consumption and lifestyle havedrawn leaders and policy makers to the rhetoric of lifelong learning. There isa growing recognition of the need to move towards lifelong learning,specifically that which focuses on informal and non-formal learning by adults.The purpose of this paper is to provide a framework for an understanding oflifelong learning as part of everyday life and its importance to development.